Preventive Criminal policy supervising sexual offenses in Islamic law - Mohammadali Elahi; Mohamadali Heidari; Mohsen Shekarchi zadeh (مطالعات فقه و حقوق اسلامی, 2021)
Islam ,in base on its attention to the inherent needs of human, has accepted proper rules for their and has set up the ways in this regard. According to Islam, marriage is the only way to modify the sexual instinct. Prohibited sexual behaviors are mentioned to as "sexual crimes." The criminal policy of Islam about sexual instinct is a moderate and realistic policy. While Islam has accepted sexual instinct as an important and vital issue in duration of life, it has proposed criminal and non-criminal measures as preventive solutions. Islam seeks to consolidate  the soul of individuals, to create an internal control force in individuals in order  to keep people away from the deviations of the sexual instinct. Next, it regulates rules to reduce the attractions and make it harder for sex offenders to commit. Finally it propose the punishments. Based on the findings of this research, by descriptive-analytical method, having chastity, self-control, having hijab, modesty, the principle of fear And hope,…etc. are among the non-criminal (social prevention) policies of Islamic jurisprudence against sexual crimes.